Dancing with Falsification: The Dynamic of Chemistry Atomistic Theories Across Centuries - Fibonacci, Anita; Kadarohman, Asep; Nahadi, Nahadi; Anwar, Sjaepul; Hernani, Hernani (Journal of Educational Chemistry (JEC), 2023)
This research aimed to explore the contribution of the falsification process to the progress of science in the field of atomic theory. The analysis focused on the history of atomic development and how this theory underwent a process of falsification. This research was qualitative research using a literature study with a narrative review method. The results showed that the development of a theory, including the theory of atoms, has undergone many improvements. Falsification is an essential aspect of scientific progress, especially in atomic theory, involving testing the theory through experimentation and observation to determine accuracy. In the development of atomic theory, falsification played a key role, as in Dalton's atomic theory. Although revolutionary, subsequent experiments revealed subatomic particles, resulting in the falsification of Dalton's ideas and the emergence of a more complex understanding of atomic structure. The evolution of atomic theory shows that scientific knowledge is dynamic, continuing to develop through falsification. New evidence continues to refine ideas, ensuring scientific knowledge accurately reflects the natural world. The scientific method emphasizes openness to falsification, stating that theories must be testable and can be replaced when significant evidence refutes the theory. This openness is the basis for scientific progress and a deeper understanding of the universe.